The effects of dietary organic selenium supplementation on physiological status of cultured marron, Cherax cainii (Austin, 2002) - Nugroho, Rudy Agung (Curtin University, 2014)
Six 90-day feeding experiments including outdoor commercial marron ponds trial were designed and conducted to investigate the effects of dietary Sel-Plex® as a source of organic selenium (OS) supplementation in marron, Cherax cainii (Austin, 2002). The effects were evaluated by measuring the growth performances, health indices, immunity responses and antioxidant enzyme activity and finally validated by comparing the marron performance results with other currently employed probiotics under outdoor commercial marron farm environment.Various marron sizes, mean initial weights of 3.6; 40 and 76 g, were used and reared inder laboratory conditions in the plastic cylindrical tanks with filtration, aeration; automatic heater and PVC pipes for shelter. The marron were fed at a rate of 3% of body weight every second day. Uneaten food and faeces were siphoned out before the next feeding and sufficient freshwater was added to maintain 70 L of water in every tank. During each experiment, water parameter such as temperature, pH, nitrate, nitrite and ammonia levels were measured once a week. To evaluate the effects of Sel-Plex® supplementation, growth and physiology parameters such as, initial and final weight; carapace and total length; specific growth rate (SGR); daily weight gain (DWG); average weekly gain (AWG); relative growth rate (RGR) and organosomatic indices were used as a tool to evaluate of OS supplementation on the marron‘s growth and health performance. Meanwhile, immune parameters such as total and differential haemocyte count (THC and DHC); neutral red dye retention time (NRRT); lysosomal membrane integrity and bacteraemia were also used as an indicator of the health of marron fed OS. Besides growth, physiological and immune indices, the health of digestive tract such as histology of midgut and hepatopancreas; condition of microvilli; amylase and protease activity of marron fed OS were assessed to examine the effects of OS supplementation.As selenium (Se) can be retained in the various tissues and influence on antioxidant enzymes activity, total Se retention in the hepatopancreas and muscle were determined in the backdrop of antioxidant enzyme activities of glutathione peroxidase (GPx), glutathione-S-transferase (GST) and lipid peroxidase (LPO) measurements.Sel-Plex® supplementation of 0.1-0.3 g kg-1 showed improvements in survival, physiological and immunological responses in the marron. The optimum level of Sel-Plex® supplementation was found at 0.2 g kg-1 of feed which improved the survival, health and immune status of the cultured marron. Dietary inclusion of Sel-Plex® also enhanced the health of the digestive system as shown by a healthier midgut and hepatopancreatic condition in term of the number of microvilli and structural improvements, respectively. In addition, marron fed 0.2 g kg-1 of Sel-Plex® also improved the digestive enzyme activity and increased resistance ability of marron against Vibrio mimicus infections. Further, dietary 0.2 g kg-1 Sel-Plex® in the diet showed higher antioxidant enzymatic activity and improved lysosomal membrane integrity, reduced LPO and higher total soluble Se retention in the muscle of marron compared to inorganic form of Se and mannan oligosaccharide (MOS). Higher levels of dietary Sel-Plex®, however, led to increased stress in the cultured marron.The LC50-96h of Sel-Plex® was calculated at 166.28 g L-1, indicating that natural presence of OS in the water is not harmful to marron. The trial in commercial ponds found that pond-water temperature was significantly higher than the temperature under laboratory conditions resulting in higher growth performances. Further, THC and total soluble Se retention in the muscle of the marron fed any supplement were higher than in marron fed the control diet under outdoor commercial environment. The pond-reared marron fed OS had significantly higher SGR and total Se retention in the muscle tissues but lower THC than laboratory-reared marron. The DHC of marron fed OS did not show significantly difference (P>0.05) between pond-reared marron and laboratory-reared marron. The present research concludes that Sel-Plex® as a source of OS can be used as a dietary supplement to improve growth and health of marron. 0.2 g kg-1 of Sel-Plex® which approximately equates to 0.4 mg kg-1 OS is suggested to be added in the basal diet in order to attain the optimum benefit of OS.